Determinants of personal bankruptcy in Malaysia / Sharifah Heryati Syed Nor - Syed Nor, Sharifah Heryati (2018)
Personal bankruptcy is on the rise in Malaysia. Malaysia Department of Insolvency reported that personal bankruptcy has increased since 2007, and the total accumulated personal bankruptcy cases stood at 131,282 in 2014. This is indeed an alarming issue because the increasing number of personal bankruptcy cases will have a negative impact on the Malaysian economy as well as on the society. From the aspect of individual's personal economy, bankruptcy minimizes their chances of securing a job. Apart from that, their account will be frozen, lost control on their assets and properties and not allowed to start any business nor be a part of any company's management. Bankrupts also will be denied from any loan application, restricted from travelling overseas, and cannot act as a guarantor. This study thoroughly investigate this problem by determining the profiles of bankruptcy cases, developing the personal bankruptcy credit scoring models, identifying the significant variables of personal bankruptcy and comparing the performance of the credit scoring models. In this study, bankrupt is defined as terminated members who failed to settle their loans. The sample comprised of 24,546 cases with 17% settled cases and 83% terminated cases. The data included a dependent variable, i.e., bankruptcy status (Y=l(bankrupt), Y=0(nonbankrupt)), and 12 predictors. Upon completion, this study succeeds to come out with the profiles of bankrupts, reliable personal bankruptcy scoring models and significant variables of personal bankruptcy. The findings of this study are very useful and significant to banks, creditors, Malaysia Department of Insolvency, potential borrowers, members of AKPK and the society in general on the awareness and the risk of personal bankruptcy and such information may help them to make personal bankruptcy prediction and to take preventive or corrective measures in reducing the number of personal bankruptcy cases. It is hoped that this study will be a cornerstone for further development and improvisation, especially as more information and data become available or accessible.